Retrospective or Look into the Future: Possibility of General Mental Giftedness Development of Senior Preschoolers - Burlakova I.A.; Klopotova E.E. (Психолого-педагогические исследования)
The article gives a brief analysis of the current state of work with gifted children in Russia and abroad. It is noted that the research of giftedness of preschool children is poorly represented in science; meanwhile nowadays there are almost no practices of research and creation of conditions for giftedness development in preschool age. In this context, to solve the stated problem, it seems reasonable to return to the past studies of the giftedness of preschool children, in particular, to consider the studies carried out in Russia under the guidance of O.M. Dyachenko and L.A. Wenger. The studies were aimed at identification of the structure of the preschoolers overall mental giftedness and at building developmental work with this category of children, and despite the fact that the studies were conducted more than 20 years ago, they remain to be relevant. The development of cognitive activity (I.A. Burlakova) as the core of general mental giftedness is considered as one of the directions of development and formation of mental giftedness of preschool children. The results of the study of E.E. Klopotova and N.S. Denisenko revealing the structure of cognitive activity of children of preschool age and the possibilities of its development are also considered in the article. The developed model of general mental giftedness of preschoolers and the studies performed in the framework of the approach of L.A. Wenger and О.M. Dyachenko confirm the possibilities of early identification of giftedness and of support of its development, taking into account the features of the age. The central element of such educational work is, along with the development of general mental and creative abilities, the creation of conditions for the development of cognitive activity. It is concluded that it is necessary to continue research of preschool giftedness and its development at the age up to 7 years basing on the theory of amplification